1868 Id. Sess. Laws 95, An Act Amendatory of an Act Entitled “An Act Concerning Crimes and Punishments," ch. 10, § 1 - (:unkn) unknown (General Publisher, 1868)
Prohibited the discharge of any gun, pistol, or any other species of firearms to willfully or maliciously disturb the peace or quiet of any neighborhood. Violators fined not exceeding two hundred dollars, or imprisoned in the County jail not exceeding two months.
--
Keywords: DISCHARGE